The thermoluminescence characteristics and the glow curves of Thulium doped silica fiber exposed to 10 MV photon and 21 MeV electron radiation - Alawiah, A.; Alina, M.S.; Bauk, S.; Abdul-Rashid, H.A.; Gieszczyk, W.; Noramaliza, M.N.; Mandiraji, G.A.; Tamchek, N.; Zulkifli, M.I.; Bradley, D.A.; Marashdeh, M.W. (Elsevier, 2015)
The thermoluminescence (TL) glow curves and kinetics parameters of Thulium (Tm) doped silica cylindrical fibers (CF) are presented. A linear accelerator (LINAC) was used to deliver high-energy radiation of 21 MeV electrons and 10 MV photons. The CFs were irradiated in the dose range of 0.2-10 Gy. The experimental glow curve data was reconstructed by using WinREMS. The WinGCF software was used for the kinetic parameters evaluation. The TL sensitivity of Tm-doped silica CF is about 2 times higher as compared to pure silica CF. Tm-doped silica CF seems to be more sensitive to 21 MeV electrons than to 10 MV photons. Surprisingly, no supralinearity was displayed and a sub-linear response of Tm-doped silica CF was observed within the analyzed dose range for both 21 MeV electrons and 10 MV photons. The Tm-doped silica CF glow curve consists of 5 individual glow peaks. The Ea of peak 4 and peak 5 was highly dependent on dose when irradiated with photons. We also noticed that the electron radiation (21 MeV) caused a shift of glow peak by 7-13 degrees C to the higher temperature region compared with photons radiation (10 MV). Our Tm-doped fibers seem to give high TL response after 21 MeV electrons, which gives around 2 times higher peak integral as compared with 10 MV photon radiation. We concluded that peak 4 is the first-order kinetic peak and can be used as the main dosimetric peak of Tm-doped silica CF. (C) 2015 Elsevier Ltd. All rights reserved.